Study on the potential of freshwater fish aquaculture in Minasatene District, Pangkep Regency, South Sulawesi Province - Andi Masriah; St. Zaenab; Andi Nur Apung Massiseng; Irwansyah Irwansyah (Akuatikisle: Jurnal Akuakultur, Pesisir dan Pulau-Pulau Kecil, 2022)
This study aimed to determine the potential of freshwater fish aquaculture in Minasatene District, Pangkep Regency, South Sulawesi Province. Data collection techniques were carried out by observing the location of freshwater fish aquaculture, interviewing respondents using questionnaires and documentation. The type of data collected is primary data, namely observation data regarding the distribution of freshwater fish aquaculture locations, types and quantities of freshwater fish production as well as supporting data through interviews with respondents of freshwater fish aquaculture business actors related to the activities carried out, then secondary data from agencies related to production results. Freshwater fish in Minasatene District. This research was conducted in Minasatene District, Pangkep Regency, South Sulawesi Province, in February – April 2021. The results of this study are the aquaculture potential of freshwater fish in the Minasatene sub-district of 1.28 tons/year/ha with the largest producer of freshwater fish coming from Minasate'ne Village and Kalabbirang Village with potential production of tilapia, catfish and koi fish. Factors affecting the production of freshwater fish aquaculture in the Minasatene sub-district are the number of abandoned freshwater fish aquaculture lands, non-optimal management, traditional management, dependence on government assistance, the influence of COVID-19, and conversion of cultivated land into tourist areas.